Conversion and the transformation of culture in the Finnish Pentecostal movement - Teemu Mantsinen (Approaching Religion, 2015)
A religious community is composed of and by its members. It both transforms and reflects their styles. This article argues that a crucial aspect of cultural change is the process of identity-making through personal experience. In the development of any evangelical religious movement its second and third generations are especially important as they have a different experience of, and identification with, their religion than does the first generation. The Finnish Pentecostal movement has changed from being a radical to a more moderate movement because it has evolved in step with its  members’ socialization. Based on my fieldwork and research I want to emphasise this difference between the experiences of the first and subsequent generations in explaining how a religious movement changes.